2003
DOI: 10.1046/j.1365-2702.2003.00841.x
|View full text |Cite
|
Sign up to set email alerts
|

Substance abuse: prevalence in a sample of nursing students

Abstract: Substance use can reduce scientific progress and academic achievement of nursing students; therefore, authorities of the university must be able to assess the extent of the problem, understand the contributing factors, recognize signs and symptoms, and use educational interventions in identifying and preventing substance dependency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 7 publications
1
20
3
Order By: Relevance
“…According to our study, a minority of drugdependent people had initiated drug use by cannabis. This is in line with the reports regarding the low prevalence of cannabis use in Iran (Ahmadi, Arabi, & Mansouri, 2003;Ahmadi & Ghanizadeh, 2000;Ahmadi & Hasani, 2003;Ahmadi, Maharlooy, & Alishahi, 2004;Day, Nassirimanesh, Shakeshaft, & Dolan, 2006;Meimandi, Nakhaee, Divsalar, & Dabiri, 2005). High proportion of initiation of substance use with opiate among Iranians may probably be due to the fact that opiate is the most used drug in this country, which increases the rate of encounter to opium as the first drug in the environment and a high rate of offer than other drugs.…”
Section: Drug Initiation Characteristicssupporting
confidence: 87%
“…According to our study, a minority of drugdependent people had initiated drug use by cannabis. This is in line with the reports regarding the low prevalence of cannabis use in Iran (Ahmadi, Arabi, & Mansouri, 2003;Ahmadi & Ghanizadeh, 2000;Ahmadi & Hasani, 2003;Ahmadi, Maharlooy, & Alishahi, 2004;Day, Nassirimanesh, Shakeshaft, & Dolan, 2006;Meimandi, Nakhaee, Divsalar, & Dabiri, 2005). High proportion of initiation of substance use with opiate among Iranians may probably be due to the fact that opiate is the most used drug in this country, which increases the rate of encounter to opium as the first drug in the environment and a high rate of offer than other drugs.…”
Section: Drug Initiation Characteristicssupporting
confidence: 87%
“…Besides the controversial findings of the studies cited here, their results might not be applicable for other cultural settings because the response pattern to sensitive questions in each community is highly dependent on cultural context of that community. In Iran, there has been a number of investigations that have assessed sensitive behaviors in specific subgroups such as ecstasy use in university students (8), sexual experience among unmarried adolescent (9), and substance use among high school girls, and nursing students (10, 11) using self-administered questionnaires. Moreover, we found that some studies used face-to-face interviews to investigate the prevalence of high-risk behaviors (12).…”
Section: Introductionmentioning
confidence: 99%
“…It is also used for enjoyment and elimination of tension [5,6]. Some Iranian patients consume opium for their diabetes, although the reasons and prevalence are not clear.…”
Section: Introductionmentioning
confidence: 99%